The intriguing strategies of Tannerella forsythia's host interaction - Schäffer, Christina; Andrukhov, Oleh (Frontiers in Oral Health, 2024)
Tannerella forsythia, a member of the “red complex” bacteria implicated in severe periodontitis, employs various survival strategies and virulence factors to interact with the host. It thrives as a late colonizer in the oral biofilm, relying on its unique adaptation mechanisms for persistence. Essential to its survival are the type 9 protein secretion system and O-glycosylation of proteins, crucial for host interaction and immune evasion. Virulence factors of T. forsythia, including sialidase and proteases, facilitate its pathogenicity by degrading host glycoproteins and proteins, respectively. Moreover, cell surface glycoproteins like the S-layer and BspA modulate host responses and bacterial adherence, influencing colonization and tissue invasion. Outer membrane vesicles and lipopolysaccharides further induce inflammatory responses, contributing to periodontal tissue destruction. Interactions with specific host cell types, including epithelial cells, polymorphonuclear leukocytes macrophages, and mesenchymal stromal cells, highlight the multifaceted nature of T. forsythia's pathogenicity. Notably, it can invade epithelial cells and impair PMN function, promoting dysregulated inflammation and bacterial survival. Comparative studies with periodontitis-associated Porphyromonas gingivalis reveal differences in protease activity and immune modulation, suggesting distinct roles in disease progression. T. forsythia's potential to influence oral antimicrobial defense through protease-mediated degradation and interactions with other bacteria underscores its significance in periodontal disease pathogenesis. However, understanding T. forsythia's precise role in host-microbiome interactions and its classification as a keystone pathogen requires further investigation. Challenges in translating research data stem from the complexity of the oral microbiome and biofilm dynamics, necessitating comprehensive studies to elucidate its clinical relevance and therapeutic implications in periodontitis management.